Current investigations on targeted therapy in renal cancer - Leśniewski-Kmak, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2005)
The review of targeted therapy in renal cancer was undertaken. Inhibition of vascular endothelial growth factor (VEGF) is one of the most interesting mechanisms of action. PTK-878 and SU-878 – antiangiogenic potency, but also with directly antitumor activity molecule are tyrosine kinase inhibitors. Phase III trial with SU-11248 in advanced disease is ongoing. BAY-43-9006 is a multitargeted agent with antiangiogenic activity. Phase III trial with subject with progression after immunotherapy is conducting. Neovastat, a multifunctional antiangiogenic agent, has been shown to inhibit the angiogenic process, and hopeful data from phase II trial. Data from phase III are not available. Bevacizumab is an anti-VEGF antibody, which was tested in phase II trial with patients with metastatic RCC. There was 10% response rate and prolongation of time to tumor progression in arm with higher dose of bevacizumab. The mammalian target of rapamycin (mTOR) is a serine/threonine kinase that has been increasingly recognized as key to the regulation of cell growth and proliferation. CCI-779 is an ester of rapamycin and inhibitor of mTOR, currently in Phase II trial with advanced renal cancer patients. Proteasome, is responsible for the majority of protein turnover through the ubiquitin-proteasome pathway. Bortezomib is designed to target the proteasome and data from phase II trial in renal cancer were published recently. Another mechanisms of action under investigations are genomic therapy and antibody against specific superficial antigens. Patients with kidney cancer need approvals of new drug, but it has to be based on data from well designed clinical trials.